Some ideas concerning Public Relations in sports organizations - Eiró-Gomes, Mafalda (2018)
This paper addresses the second phase of an ongoing project that involves mixed methods analysis and that has as its main purpose to understand the role of the communication professionals in the third sector, or what some authors call, the non-for-profit sector (Neto, et al., 2017). Moreover, the way these organizations understand what can be considered under the scope of the functions of these professionals was also under investigation. After a work that dealt with the mainstream of the area, the Non-Governmental Organisations for development, the researchers turned their look to almost an unknown field, the national sports federations. These are important actors in the civil society in Portugal, as in so many other countries, due to the fact that they are responsible entities for the promotion of sports at all levels of society.